2021
DOI: 10.1177/17479541211001879
|View full text |Cite
|
Sign up to set email alerts
|

Does context matter? Unpacking differences in program quality and developmental experiences across competitive and recreational youth sport

Abstract: To date, little research has explored differences between competitive and recreational youth sport contexts beyond descriptions of inherent features. The purpose of this exploratory study was to examine if differences existed between competitive and recreational youth sport on (a) observed quality delivery and (b) youth’s perceptions of basic psychological needs satisfaction and developmental experiences. Forty-six youth sport teams participated in the study from competitive ( n = 23) and recreational contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recreational sport is provided in the community by paid or volunteer sports coaches or with family, friends, or peers and provides opportunities to enhance wellbeing without the expectation of high-level performance. 77 , 78 As recreational sport is not constrained by the strict rules that apply to competitive sport, there is greater flexibility to accommodate varying needs of people with disabilities by modifying components of the activity or environment. This flexibility is beneficial to people with disabilities who may be unable to perform a sports activity in the same way as their able-bodied peers, or whose abilities may fluctuate over time.…”
Section: Stages Of the Sports Participation Frameworkmentioning
confidence: 99%
“…Recreational sport is provided in the community by paid or volunteer sports coaches or with family, friends, or peers and provides opportunities to enhance wellbeing without the expectation of high-level performance. 77 , 78 As recreational sport is not constrained by the strict rules that apply to competitive sport, there is greater flexibility to accommodate varying needs of people with disabilities by modifying components of the activity or environment. This flexibility is beneficial to people with disabilities who may be unable to perform a sports activity in the same way as their able-bodied peers, or whose abilities may fluctuate over time.…”
Section: Stages Of the Sports Participation Frameworkmentioning
confidence: 99%
“…In the distribution of articles based on context, several studies related to recreational sports policies in development through sports were found, divided into several aspects, including:  Recreational Sports [32]- [35]  Sports Policy [36]- [40]  Development Through Sport [41]  Sport Policy, Development Through Sport [6], [11], [21], [42], [43]  Sport Policy, Recreational Sport [4], [7], [18], [44]- [47] Advances in Health Sciences Research, volume 45…”
Section: Distribution Of Articles By Contextmentioning
confidence: 99%
“…Based on the type of data in each article, several methods are often used in this study, including:  Case Study [4], [11], [39], [43]  Comparative Analysis [6], [18], [21], [35], [37], [38], [42], [44]  Experiment [33], [40], [47]  Mix Methods [7]  Survey [32], [34], [45]  Systematic Literature Review [36], [41], [46], [48] The method most often used in research related to the context of recreational sports policy in development through sports is a comparative analysis study, where the study is compared to the increase in community participation in sports. The distribution of articles by data type is presented in Figure 5.…”
Section: Distribution Of Articles By Data Typementioning
confidence: 99%
See 1 more Smart Citation